Manajemen Kebijakan Pemerintah dalam Mewujudkan Wisata Islami di Pantai Kabupaten Aceh Timur - Ismail; Muliana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Sharia Tourism refers to a form of tourism that adheres to Islamic principles, emphasizing not only the attractiveness of destinations but also ensuring management complies with Islamic guidelines. The development of sharia-based tourism has become an essential need for both national and global communities, significantly contributing to economic development. This study aims to analyze government policy management in developing Islamic tourism at the beaches of East Aceh Regency. A descriptive analytical method with a qualitative approach was employed to identify a model for local government policies. The findings reveal that while the cleanliness of the beaches is well-maintained, service management requires improvement, and visitors have not fully complied with sharia-based regulations. The East Aceh Regency Government has begun implementing regulations through the Islamic Law Office and Wilayatul Hisbah; however, a comprehensive policy framework is not yet established. Challenges include limited budgets, insufficient supervisory personnel, and low public awareness of Islamic tourism. Strategic efforts include socialization, evaluation, and strengthening collaboration among stakeholders to support the sustainable development of Islamic tourism.